Make work healthy create a sustainable organization with high-performing employees - Ryan, John S.; Burchell, Michael J. (Wiley, 2023)
Work Healthy is a why-to/how-to book to deliver higher organizational performance through a new approach to workforce management. It provides organizations, leaders and managers with the knowledge, model, and methodology to radically change their current approach delivering a resilient and sustainable system of operation. The authors have discovered that the key priorities of organizations, from covid recovery, DEI, wellbeing, mental health management, belonging, purpose, sustainability can all be achieved by focusing on health in its broadest sense. However, individuals have defined health too narrowly and organizations have got their current approach badly wrong and in turn are wasting time, money, and resources. But worst of all they are missing the ultimate driver of performance. Organizations need to move away from an ad-hoc, tick-box, tactical, short-term, programmatic, awareness building, approach to employee health solely focused on reducing illness and absence to a more strategic, data driven, evidence-based, systematic, and cultural approach focused on building work capacity and sustainability. The book also uncovers the symbiotic relationship between organization health and employee?s health. The data collected from over 30+ organizations (including Salesforce, Nike, British Telecom, Telefonica, Sky Television, Pasa Brazil, Vattenfall Sweden, Takeda Pharmaceuticals, etc.) with 30k+ survey responses has identified game changing correlations. The health of the organization impacts the health of individuals, and the health of the individuals impacts the health of the organization"--